Factores de riesgo para las enfermedades periodontales (2010)
ABSTRACT: Periodontitis are multi-factorial diseases that affect susceptible individuals. Microbial dental plaque bio-film is the main etiological factor, although several other local and systemic factors have important modifying roles on its pathogenesis. Those risk factors are associated with the disease, but they do not necessarily cause it. Numerous risk factors do exist, but only a few of them have scientific evidence that show a causal relationship with periodontitis. The purpose of this article is to make a brief review on of the most relevant literature related to risk factors in periodontitis and to develop a multi-factorial risk approach that emphasizes on the importance of prevention as a work plan in the area of periodontology. Methods: publications of the last ten years were reviewed. Results: based on controlled longitudinal studies, the risk factors identified were: smoking habit, Diabetes Mellitus with low glycemic control, and colonization of tissue by a high number of specific bacteria. Conclusion: risk factors may have a significant role on the pathogenesis of periodontitis. Effective disease management should include identification and control of risk factors.